Whole blood transcriptome profiling identifies candidate genes associated with alopecia in male giant pandas (Ailuropoda melanoleuca) - Haibo Shen; Caiwu Li; Ming He; Yan Huang; Jing Wang; Jing Luo; Minglei Wang; Bisong Yue; Xiuyue Zhang (BMC Genomics, 2022)
Abstract Background The giant panda (Ailuropoda melanoleuca) is a threatened species endemic to China. Alopecia, characterized by thinning and broken hair, mostly occurs in breeding males. Alopecia significantly affects the health and public image of the giant panda and the cause of alopecia is unclear. Results Here, we researched gene expression profiles of four alopecia giant pandas and seven healthy giant pandas. All pandas were approximately ten years old and their blood samples collected during the breeding season. A total of 458 up-regulated DEGs and 211 down-regulated DEGs were identified. KEGG pathway enrichment identified that upregulated genes were enriched in the Notch signaling pathway and downregulated genes were enriched in ribosome, oxidative phosphorylation, and thermogenesis pathways. We obtained 28 hair growth-related DEGs, and identified three hub genes NOTCH1, SMAD3, and TGFB1 in PPI analysis. Five hair growth-related signaling pathways were identified with abnormal expression, these were Notch, Wnt, TGF-β, Mapk, and PI3K-Akt. The overexpression of NOTCH1 delays inner root sheath differentiation and results in hair shaft abnormalities. The delayed hair regression was associated with a significant decrease in the expression levels of TGFB1. Conclusions Our data confirmed the abnormal expression of several hair-related genes and pathways and identified alopecia candidate genes in the giant panda. Results of this study provide theoretical basis for the establishment of prevention and treatment strategies for giant pandas with alopecia.